A compliant guiding mechanism utilizing orthogonally oriented flexures with enhanced stiffness in degrees-of-constraint. (January 2022) - Li, Ruiqi; Yang, Zhijun; Cai, Bingyu; Chen, Guimin; Wu, Baisheng; Wei, Yutai
Highlights: A guiding mechanism is designed to enhance the stiffness along the DOC. The nonlinearity of the guiding mechanism is modeled for large-stroke applications. The model improves the kinetostatic accuracy of a beam with fillets effectively. Simultaneous optimal design of topology and size is proposed for the mechanism. Experiments are carried out to illustrate the efficiency of the proposed mechanism. Abstract: The large stroke is usually realized by lowering stiffness along the degrees of freedom, which usually leads to a decrease of stiffness along the degrees of constraint. A high stiffness ratio is crucial for reducing the deflections induced by disturbances such as eccentric force and the gravity of the load. Besides, the fatigue life of these mechanisms will be shortened due to the large stress caused by the large deflection. This paper proposed a new guiding mechanism using orthogonally oriented flexures to improve the stiffness along the degrees of constraint and reduce stress concentration. The energy method is utilized to obtain the kinetostatic model of the guiding mechanism by taking the nonlinear deflection into account, based on which the mechanism is optimized by simultaneously considering the topology and size. As compared to the performance of traditional design obtained through the same optimization objective and constraints, the optimal design effectively improves the stiffness along the degrees of constraint, whose accuracy is also validated by the finite element analysis results. Experimental results show that the proposed mechanism increases the stiffness ratio K a z / K x by 3.54 times compared to the traditional mechanism.